Recombination X-ray radiation from plasma linersa; Technical Physics Letters; Vol. 31, iss. 7 - Oreshkin V. I. Vladimir Ivanovich; Baksht R. B.; Labetskii A. Yu.; Ratakhin N. A. Nikolay Aleksandrovich; Russkikh A. G.; Chaikovsky S. A.; Fedyunin A. V.; Shishlov A. V. (2005, 2005)
Title screen